Rancangan Model Sistem Informasi Terintegrasi Pada Bagian Admin Gudang E-Commerce - Rizki Alifnur Harmawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Abstract Inventory is a company resource that involves special handling in managing it. In the e-commerce warehouse admin section, PT Mendekor Anugerah Indonesia has a role in managing inventory in the company and is responsible for customer orders. During the research, it was found that the product search process was time-consuming because the inventory recording system had not been well integrated. The research aims to solve problems using the method of interrelationship diagrams, propose improvements to warehousing activities, and design the Waterfall Model information system development. Based on solving the problem, it was found that the root of the problem was that the information system had not been integrated. The results of solving the problem submitted a proposal to create an information system in the process of warehouse activities. The information system is based on the Waterfall Model with Unified Modeling Language, the design consists of use case diagrams, activity diagrams, and sequence diagrams. The system design uses Microsoft Access as a database application. The database system assists the warehouse admin in managing inventory and monitoring warehouse activities. The implementation of the proposed improvements is expected to facilitate the search for goods in the warehouse and the management of goods data. Keywords: Information Systems, Interrelationship Diagrams, Waterfall Models, Unified Modeling Language.